TO AGGRESSIONS, WE (RE)EXIST WITH THE ENVIRONMENTAL CULTURE OF OUR AMERICA - Villela, Fábio Fernandes (Seven Editora, 2025)
This text presents the results of the research entitled: "Environmental culture in rural education: landscape, history and traditional knowledge of the countryside territory", carried out between 2016 and 2019, where it was possible to research the environmental culture of the northwest of São Paulo – SP, from the point of view of its sustainable development. The general objectives of the research were to investigate the landscape, history and traditional knowledge of the countryside territory and as specific objectives, the education of young people and adults (EJA). As for the theoretical-methodological framework, work projects were used. The results were the articulation of knowledge with the different areas of knowledge, enabling the experience of new values, the triggering of collective actions, as well as the increase in schooling associated with social and professional qualification, enabling new learning. DOI: https://doi.org/10.56238/sevened2024.037-189